Co Nanoparticles Encapsulated in Nitrogen Doped Carbon Tubes for Efficient Hydrogenation of Quinoline under Mild Conditions. Issue 1 (8th November 2019) - Yun, Ruirui; Hong, Lirui; Ma, Wanjiao; Zhang, Ruiyu; Zhan, Feiyang; Duan, Jingui; Zheng, Baishu; Wang, Suna
Abstract: The hydrogenation of nitrogen‐containing heterocyclic precursors in aqueous medium is quite challenging, especially at low temperature and without imposing molecular hydrogen pressure. In the light of the edges of metal nanoparticles (NPs) possess high selective activity, but most of the exposed metal surface does not. Hence, to influence the activity of the entire NPs surface, the use of zeolitic imidazolate frameworks (ZIFs) to obtain the metal NPs encapsulated in the carbon tubes which has been applied frequently. Herein, we design and synthesize a series of metal catalysts encapsulated in N‐doped carbon nanotubes (NCT), which disperse on the hollow N‐doped carbon framework (HNC), via pyrolysis ZIF‐67, ZIF‐67@ZIF‐8, and ZIF‐8@ZIF‐67 step by step. The catalyst of Co@NCT/HNC shows outstanding activity of hydrogenation of quinoline under mild conditions, due to the synergistic effects between Co NPs, NCT and HNC, such as the NCT make the hydrogen reach the surface of the reactant rapidly, and the encapsulated structure can enormously prevent the metal aggregating. Abstract : Photocatalysis : The Co@shell loaded on hollow nitrogen doped carbon frameworks (Co@NC/HNC), dispersed on the inner face of HNC (Co@NC), and encapsulated in nitrogen doped carbon tube dispersed on the HNC (Co@NCT/HNC) catalysts have been designed and synthesized by ZIF‐67, ZIF‐67@ZIF‐8 and ZIF‐8@ZIF‐67 as sacrificial templates.